Prevalence of medication errors at outpatients pharmacy, Hospital Melaka - Mansur Huang, Mohamad Hafiz; Amat, Qhalida; Jamil, Azwa (2013)
The types of medication error and possible prevalence factor of medication error is reviewed. A medication error is generally defined as a deviation from the physician's medication order as written on the patient's prescription. In hospitals, medication errors occur at a rate of about one per patient per day. Our study has done in outpatient department of Hospital Melaka. The study discovers the percentages of errors occur and the possible prevalence factor based on types of error. The result of the study can be used as the guideline to reduce the medication error especially the prescription error and improve the service quality of dispensing process in outpatient pharmacy. The data focused on filling error, labelling error and prescribing errors which were dose error, dosage form error and omission error. The retrospective method was used to carry out the study. The days were chosen randomly and the data will be collected by marking the errors according to their types of medication error. The 'Medication Error Form' also being recorded by the pharmacist for our reference. Based on 4850 prescription that being collected, all the data received was 'key in' into the SPSS and Microsoft Excel. The average of error occurs per day was 2.38%. The most error occurs was prescribing error which was 79% whereas the lowest error occurs was labelling error which was 1 %. Percentage of filling error was 20%. The possible prevalence factors are being examined based on the result. Instead, this study will be fully used soon as determination main factor of medication error.